Anticardiolipin antibodies: isotype distribution and phospholipid specificity. Issue 1 (January 1987) - Gharavi, A E; Harris, E N; Asherson, R A; Hughes, G R
Abstract : Quantitative isotype specific enzyme linked immunosorbent assay (ELISA) was used to determine the distribution of immunoglobulin isotypes and phospholipid specificities of anticardiolipin (anti-CL) antibodies in 40 patients with one or more of the following 'antiphospholipid (anti-PL) antibody associated clinical complications'--namely, thrombosis, fetal loss, thrombocytopenia. Twelve of 40 patients had IgG, IgM, and IgA anti-CL antibodies. Ten patients had IgG and IgM, five patients had IgG and IgA, and three patients had IgM and IgA anti-CL antibodies. There was no statistical association between any single isotype or any group of isotypes with thrombosis, fetal loss, or thrombocytopenia. The presence of IgG anti-CL antibodies in 36 of the 40 patients suggests that this isotype may be most important in determining clinical complications, but there were four patients without IgG anti-CL antibodies who also appeared susceptible to thrombosis, fetal loss, and thrombocytopenia. IgG, IgM, and IgA anti-CL antibodies bound the negatively charged phospholipids, phosphatidylserine and phosphatidylinositol, but not the zwitterionic phospholipid, phosphatidylcholine. There was no significant difference between binding to cardiolipin and binding to other negatively charged phospholipids, suggesting that the specificity of these antibodies is for negatively charged phospholipids in general rather than for cardiolipin in particular.